Defiant dads : fathers' rights activists in America - Crowley, Jocelyn Elise, 1970- (Cornell University Press, 2008)
Publisher's description -- All across America, angry fathers are demanding rights. These men claim that since the breakdown of their own families, they have been deprived of access to their children. Joining together to form fathers' rights groups, the mostly white, middle-class men meet in small venues to speak their minds about the state of the American family and, more specifically, to talk about the problems they personally face, for which they blame current child support and child custody policies. Dissatisfied with these systems, fathers' rights groups advocate on behalf of legal reforms that will lower their child support payments and help them obtain automatic joint custody of their children. In Defiant Dads, Jocelyn Elise Crowley offers a superbly balanced examination of these groups in order to understand why they object to the current child support and child custody systems; what their political agenda, if enacted, would mean for their members' children or children's mothers; and how well they deal with their members' interpersonal issues concerning their ex-partners and their role as parents. Based on interviews with more than 150 fathers' rights group leaders and members, as well as close observation of group meetings and analysis of their rhetoric and advocacy literature, this important book is the first extensive, in-depth account of the emergence of fathers' rights groups in the United States. A nuanced and timely look at an emerging social movement, Defiant Dads is a revealing investigation into the changing dynamics of both the American family and gender relations in American society.